Peningkatan Skill Opinion Mahasiswa Pendidikan Ekonomi Menggunakan Model Pembelajaran Debat - Setiaji, Cahyo (Antroposen: Journal of Social Studies and Humaniora, 2022)
Abstract: The purpose of this research is to develop the skill opinion of Economic Education students using the debate learning model. Pre-cycle observation results in students' opinion skills that are still at a low level of interpretation so that efforts are needed to improve it. The research subjects were 25 students of Economics Education who took Social Studies courses. Collecting research data using the observation method with a checklist sheet on each indicator. The research was carried out in two main cycles with 2 meetings in each cycle. The results showed that the debate model was able to improve opinion skills, both specifically and in general. Specifically, an increase in each indicator is known from the comparison of the average results of the pre-cycle, cycle 1, and cycle 2 stages on each indicator. Indicators of tolerance, courage, and substantive have a very significant increase from the low category to very high. The indicators of confidence and sentence structure increased from low to high level in cycle 2. The increase in opinion skills in general also experienced a very significant increase from the pre-cycle stage with a low level of interpretation to very high in cycle 2. In general, opinion skills of pre-cycle students included the level of interpretation. low with a success rate of 40%, increased to high in cycle 1 with a success rate of 60%, and again increased in a very high level of interpretation in cycle 2 with a success rate of 92%.